TINJAUAN HUKUM TENTANG TINDAK PIDANA JUDI TOGEL JENIS PAKONG (STUDI KASUS PUTUSAN NOMOR 784/PID.B/2019/PN TNG - Chairul Anwar; Nurmalia Ihsana (The Juris, 2022)
According to the Big Indonesian Dictionary, Gambling is risking a certain amount of money or property in a guessing game based on chance, with the aim of getting an amount of money or property that is greater than the original amount of money or property. Gambling is a phenomenon that cannot be denied in society. The act of gambling in Indonesian society can be found in various layers of society. There are also various forms of gambling, from traditional ones such as dice gambling, cockfighting and others such as the Pakong Type Togel Gambling which the author uses as a case study. The problem in this paper is how is the legal arrangement related to the crime of gambling? And what is the basis for the consideration of the Panel of Judges case Number 784/Pid.B/2019/PN Tng? The research method used is a normative research method that focuses on library research to obtain secondary data from legal materials. The normative approach is carried out by reviewing the applicable provisions or laws and regulations. The results of the study show that legal provisions related to the crime of gambling are formulated in Article 303 and Article 303 bis of the Criminal Code. The considerations of the Panel of Judges in dropping the criminal case number 784/Pid.B/2019/PN Tng are appropriate, namely by fulfilling all the elements in the indictment of Article 303 paragraph (1) 2nd of the Criminal Code, in addition to this being based on witness testimony, the defendant's statement, and evidence coupled with the conviction of the judge. In addition, the Panel of Judges in deciding cases considered mitigating and aggravating matters for the defendants.